Relationship between indices of circulating blood cells and bone homeostasis in osteoporosis - Li, Yuan; Hao, Weimin; Guan, Jianming; Li, Bo; Meng, Li; Sun, Shuangjiao; Sheng, Tianyuan; Dong, Shuangxi; Zhou, Qian; Liu, Mingjie; Zhang, Zhongkai; Shen, Tao; et al. (Frontiers in Endocrinology, 2022)
Bone development have been shown to play an important role in regulating hematopoiesis as one major component of bone marrow microenvironment. Recent studies support the notion that there is an intricate relationship between hematopoiesis and bone homeostasis, however, little is known about the alterations in the hematopoietic lineages in pathologic conditions. Using various osteoporotic mouse models, we show here that bone microarchitecture abnormalities alter parameters of peripheral blood cells. The level of white blood cells is dynamics and negatively correlated with bone mineral density during the progression of osteoporosis. Furthermore, our clinical data confirm that osteoporosis is associated with abnormal circulating blood cell counts. These results demonstrated a causal link that osteoporosis is accompanied by the altered circulating blood cells, supporting the idea of a close interplay between hematopoiesis and bone homeostasis. Our study would propose that routine complete blood count might be applied as a potential diagnostic and putative marker for osteoporosis.